Detection and rapid recovery of the Sutter's Mill meteorite fall as a model for future recoveries worldwide. (4th March 2014) - Fries, Marc; Le Corre, Lucille; Hankey, Mike; Fries, Jeff; Matson, Robert; Schaefer, Jake; Reddy, Vishnu
Abstract The Sutter's Mill C‐type meteorite fall occurred on 22 April 2012 in and around the town of Coloma, California. The exact location of the meteorite fall was determined within hours of the event using a combination of eyewitness reports, weather radar imagery, and seismometry data. Recovery of the first meteorites occurred within 2 days and continued for months afterward. The recovery effort included local citizens, scientists, and meteorite hunters, and featured coordination efforts by local scientific institutions. Scientific analysis of the collected meteorites revealed characteristics that were available for study only because the rapid collection of samples had minimized terrestrial contamination/alteration. This combination of factors—rapid and accurate location of the event, participation in the meteorite search by the public, and coordinated scientific investigation of recovered samples—is a model that was widely beneficial and should be emulated in future meteorite falls. The tools necessary to recreate the Sutter's Mill recovery are available, but are currently underutilized in much of the world. Weather radar networks, scientific institutions with interest in meteoritics, and the interested public are available globally. Therefore, it is possible to repeat the Sutter's Mill recovery model for future meteorite falls around the world, each for relatively little cost with a dedicated researcher. Doing so will significantly increase the number of fresh meteorite falls available for study, provide meteorite material that can serve as the nuclei of new meteorite collections, and will improve the public visibility of meteoritics research.